Gender, metacognitive intervention, and dialogic interaction: EFL multimedia listening. (February 2022) - Fakhri Alamdari, Ebrahim; Bozorgian, Hossein
Abstract: This study investigated the combined effect of gender, metacognitive intervention, and dialogic interaction on Iranian EFL learners' multimedia listening comprehension and their metacognitive awareness. The data were collected through 1080 male and female Iranian advanced learners, ranging from 18 to 24 years of age, in four experimental and two control groups. Two of the experimental groups of male and female students (N = 360) received metacognitive intervention through dialogic interaction (MIDI), two of the experimental groups of male and female students (N = 360) received metacognitive intervention only (MI), and the two control groups of male and female students (N = 360) were trained through regular classroom listening activities without receiving the structured intervention program. Multimedia listening tests and the Metacognitive Awareness Listening Questionnaire (MALQ) were used to track the advanced learners' multimedia listening comprehension and metacognitive awareness. The results showed that female EFL learners in both experimental groups outperformed their male counterparts in multimedia listening comprehension and metacognitive awareness in listening. The results also revealed that the EFL learners in experimental group one (MIDI) outperformed their peers in experimental group two (MI) in both multimedia listening and metacognitive awareness. Therefore, the effectiveness of gender and dialogic interaction can be deemed as two major contributions of this study.